Treating Avoidant Personality Disorder With Combined Individual Metacognitive Interpersonal Therapy and Group Mentalization-Based Treatment: A Pilot Study. Issue 3 (26th March 2022) - Simonsen, Sebastian; Popolo, Raffaele; Juul, Sophie; Frandsen, Frederik Weischer; Sørensen, Per; Dimaggio, Giancarlo
Abstract : Supplemental digital content is available in the text. Abstract: Avoidant personality disorder (AvPD) is a severe but understudied condition. The current pilot project reports data on acceptability and outcomes of a novel treatment combining biweekly individual metacognitive interpersonal therapy (MIT) and weekly mentalization-based therapy (MBT) group therapy. A total of 30 patients with AvPD were consecutively included in the program. The primary outcome was AvPD-specific personality functioning measured by self-report after treatment. Secondary outcomes were symptom distress, interpersonal problems, quality of life, and psychosocial functioning. Twenty-two patients completed treatment, with a mean duration of 13 months. On the primary outcome, effect sizes were generally moderate to large (effect size range: 0.59–1.10). On secondary outcomes, effect sizes were large (effect size range: 0.77–2.3). Both in terms of acceptability and outcomes, results are promising for the combination of MIT and MBT for AvPD. The approach is a strong candidate for further investigation in future large-scale randomized controlled trial.